Improve the mortgaged real estate valuation at joint stock commercial bank for investment and development of Viet Nam – So giao dich 1 Branch - Nguyễn, Minh Hai (2020)
Provide basic theoretical issues onthe real estatevaluation, mortgagedreal estatevaluation of commercial banks.-Analyze the current situation of mortgagedreal estatevaluation at BIDV -So Giao Dich 1 Branchbetween2016 and2018. Indicate the achieved results but also clarifythe limitations and their causes in the valuation of mortgagedreal estateat the branch.-Proposea number of solutions to improvethe mortgagedreal estatevaluation at BIDV -So Giao Dich 1 Branchby2025